Edukasi dan Pemanfaatan Penanaman Toga Ceria sebagai Apotek Hidup di Lingkungan Sekolah SD N 1 Demulih - Ni Luh Putu Nita Miliana Indrayanti (Guruku: Jurnal Pendidikan dan Sosial Humaniora, 2024)
This study aims to provide education and utilize the Toga Ceria planting program as a living pharmacy at SD N 1 Demulih. This program aims to improve students' understanding of various medicinal plants, while maximizing the use of empty land at school as a means of learning and health. Through this activity, students are taught how to plant, care for, and utilize medicinal plants as natural remedies. The research method used is descriptive qualitative, with data collected through observation, interviews, and documentation. The results of the study indicate that planting Toga Ceria not only improves students' understanding of the benefits of medicinal plants, but also encourages independence, entrepreneurial spirit, and concern for the environment. This program plays an important role in introducing natural medicine to students and supporting health and environmental preservation in schools.